Burkitt Lymphoma Presenting as Unilateral Deafness in an Immunocompetent Patient - Andre Pinto; Offiong Francis Ikpatt; Jennifer Chapman-Fredericks (Case Reports in Medicine)
A 55-year-old HIV-negative white male presented with right ear deafness, right axillary lymphadenopathy, and weight loss. Laboratory findings included anemia, marked leukocytosis, and thrombocytopenia. Examination of the peripheral smear demonstrated the presence of increased circulating blast-like cells of intermediate size, with basophilic cytoplasm and nuclei with open chromatin. MRI of the brain was compatible with hemorrhagic labyrinthitis. Excisional biopsy of the axillary mass revealed an enlarged lymph node with effaced architecture and “starry sky” appearance. The cells expressed CD20, CD10, BCL6, and surface kappa immunoglobulin light chain, with a high proliferative index by immunohistochemistry and flow cytometry. Subsequent bone marrow biopsy was hypercellular (approximately 95%), with blast-like cells virtually replacing all hematopoietic elements. Routine karyotype as well as FISH analysis of bone marrow cells demonstrated rearrangement of the MYC gene at chromosome 8q24 region, IGH/MYC fusion, and additional signal for IGH gene. We present herein a case of sporadic Burkitt lymphoma occurring in a previously healthy HIV-negative male. The unusual clinical findings in this case include the relatively older age at presentation (55 years), an immunocompetent patient who had nodal involvement and leukemic phase of Burkitt, coupled with partial deafness. A brief educational review of this neoplasm is made.